2019
DOI: 10.3889/oamjms.2019.013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Calcium Levels in Groundwater and Dental Caries in the Coastal Population of an Archipelago Country

Abstract: BACKGROUND:The coastal region is the largest region in Indonesia as a country of the archipelago. Characteristics of groundwater content in coastal areas are very influential on dental health, especially dental caries. The main elements contained in 1-1000 mg/litre groundwater are calcium, magnesium, sodium, potassium, chlorine, bicarbonate, and sulfate groups. Calcium is an essential ingredient for living organisms that play a role in the formation of bone and tooth along with permeability of cell walls.AIM:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…Higher calcium concentrations are found in groundwater recharged in wetlands, especially in infiltrated surface water [22]. Calcium is an essential ingredient for living organisms that play a role in bone and teeth formation, along with permeability of cell walls [23]. The continuous high intake of calcium may cause stone problem [24].…”
Section: Calcium (Ca 2+ )mentioning
confidence: 99%
“…Higher calcium concentrations are found in groundwater recharged in wetlands, especially in infiltrated surface water [22]. Calcium is an essential ingredient for living organisms that play a role in bone and teeth formation, along with permeability of cell walls [23]. The continuous high intake of calcium may cause stone problem [24].…”
Section: Calcium (Ca 2+ )mentioning
confidence: 99%
“…It is known that calcium and magnesium are essential cations for health, as these are involved in many biochemical processes of the body [36,37]. It has also been reported that high levels of calcium in drinking water result in a low occurrence of dental caries [38], hypertension [39], and cardiovascular diseases [40,41]. However, there are other studies which indicate that excess calcium sometimes may result in an increased risk of myocardial infarction among postmenopausal women [42].…”
Section: Discussionmentioning
confidence: 99%
“…There are also just a few studies on the effects of Ca and Mg on the resistance and susceptibility of teeth to demineralization. 2,3 Dental caries has become a public health issue in the last decades. The problems are rooted in the consumption of fluoridated water and foods prepared with excessive fluoride salt, practices that can cause dental fluorosis.…”
Section: Correspondencementioning
confidence: 99%